eHealth Literacy in Otolaryngology Patients - Christopher Eric Bailey; William J. Kohler; Chadi Makary; Kristin Davis; Nicholas Sweet; Michele Carr (Annals of Otology, Rhinology & Laryngology, 2019)
Objectives: The aim of this study was to compare eHealth literacy—one’s perception of one’s ability to use the Internet for health care—among otolaryngology patients in 3 geographic settings of the same department. Setting: An academic otolaryngology department. Method: Patients’ opinions and perceptions of their eHealth literacy were assessed with a validated paper survey administered in the summer of 2017. Results: Of 381 asked, 351 people completed the survey, 149 at a university town teaching hospital clinic (group A), 101 at a nearby rural clinic (group B), and 101 at a remote rural clinic (group C). Mean scores were 30.80, 28.97, and 29.03 for groups A, B, and C, respectively. The overall mean was 29.76 ± 5.97. Three surveys reported the minimum score of 8, and 26 reported the maximum score of 40. Results were statistically significantly different among all sites ( P = .001), between groups A and B ( P = .027), and between groups A and C ( P = .0175). Women reported higher eHealth literacy (30.13 ± 6.27) than men (28.87 ± 5.11) ( P = .045). Participant age and role (patient or parent of a patient) were statistically insignificant. Mean scores were similar to those previously reported in other patient populations. Conclusions: Otolaryngology patients in a university town had better eHealth literacy than patients in more rural settings, suggesting that online medical resources and access points are less likely to be useful in rural populations.